Patterns of mortality among adults with intellectual and developmental disabilities in Ontario - Stankiewicz, Elizabeth (Can J Public Health, 2018)
OBJECTIVES: To determine recent mortality rates among Ontarian adults with intellectual and developmental disabilities (IDDs) and investigate changes over time in contrast to the general population. To determine the most commonly reported underlying causes of death and explore related coding practices. METHODS: Using linked health administrative data, four cohorts of adults with IDD aged 25–99 living in Ontario were followed for 1 year (one cohort for each year between 2011 and 2014). Deaths (2011 to 2014) and causes of death (2011 to 2013) were identified, and age-standardized mortality rates were calculated annually. For 2013, overall and sex-specific standardized mortality ratios (SMRs) were calculated. Mortality ratios were also examined across 5-year age groups. Commonly reported causes of death were tabulated by ICD-10 chapter, differences by sex examined, and cause-specific SMRs calculated. All deaths with IDD diagnostic codes reported as underlying cause of death were identified. RESULTS: Mortality rates among individuals with IDD have been decreasing over time; in 2014, the mortality rate was 22.6 deaths per 1000 person-years. Disparities in mortality rates relative to the general population decreased with increasing age. Men with IDD had higher mortality rates than women with IDD. The most common causes of death among individuals with IDD were cardiovascular disease, neoplasms, and diseases of the respiratory system. An IDD diagnostic code was reported as cause of death in 3.8% of cases. CONCLUSIONS: The ongoing excess mortality among Ontarians with IDD should be closely monitored by policy makers and service providers. Attention to cause of death reporting should be considered so that cause of death can be thoroughly examined.